2021
DOI: 10.1093/eurheartj/ehab724.2720
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV2 infection: functional and morphological cardiopulmonary changes in elite handball players

Abstract: Background There is increasing evidence of cardiac involvement in SARS-COV-2 infections. This may not only apply to symptomatic infections but may also affect asymptomatic athletes. This study aimed to characterize the possible acute cardiac involvement of SARS-COV-2 infection in athletes both morphologically and functionally. Methods and results Eight elite handball players (27±3.5 y) with past SARS-COV-2 infection were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…Moreover, no association between days of infection and ΔFVC, ΔFEV 1 , ΔFEV 1 /FVC, and ΔPEF was observed, even though the small sample size tested ( n = 10) and a narrow range of both dependent and independent variables may have hindered some associations. These findings suggest that COVID‐19 does not considerably affect FVC, FEV 1 , FEV 1 /FVC, and PEF in athletes with mild symptoms, which is in line with previous investigations (Fikenzer et al, 2021; Milovancev et al, 2021), but in contrast with others (Gervasi et al, 2021; Komici et al, 2021). No evidence of spirometric impairments was also observed in a large cohort of healthy young adults who had mild‐to‐moderate COVID‐19 symptoms (Mogensen et al, 2022), suggesting that spirometric impairments would unlikely occur in young and healthy populations.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, no association between days of infection and ΔFVC, ΔFEV 1 , ΔFEV 1 /FVC, and ΔPEF was observed, even though the small sample size tested ( n = 10) and a narrow range of both dependent and independent variables may have hindered some associations. These findings suggest that COVID‐19 does not considerably affect FVC, FEV 1 , FEV 1 /FVC, and PEF in athletes with mild symptoms, which is in line with previous investigations (Fikenzer et al, 2021; Milovancev et al, 2021), but in contrast with others (Gervasi et al, 2021; Komici et al, 2021). No evidence of spirometric impairments was also observed in a large cohort of healthy young adults who had mild‐to‐moderate COVID‐19 symptoms (Mogensen et al, 2022), suggesting that spirometric impairments would unlikely occur in young and healthy populations.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, players reduced their match intensity by 4.1% ± 3.5% after COVID‐19. These findings confirm and extend the results of Fikenzer and colleagues (Fikenzer et al, 2021), who observed performance impairments in male elite handball players after COVID‐19. Additionally, we observed that “general fatigue” and “muscle fatigue” symptoms were perceived by several players (77% and 54%, respectively) even following COVID‐19, suggesting that these symptoms may have played a key role in affecting players’ performance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations